Primary malignant melanoma of the urethra in women: About a case - Kaboré, Fasnewinde Aristide (Urol Case Rep, 2020)
Primary malignant melanoma of the urethra in women is a rare tumor with a poor prognosis. We report the case of a 48-year-old patient who consulted for a mass in the urethral meatus associated with symptoms of the lower urinary tract. The result of the biopsy of the mass revealed a malignant melanoma confirmed by immunohistochemistry. The extension workup was negative. She had a total cystectomy with lymph node dissection done. The one-year follow-up was without particularity.